The Effect of the Mastery Learning Model on Learning Outcomes and Collaboration Skills Elementary School Students - Roni Wahyu Wandani; Sutisna Permana; Wisnu Zakaria; Wahyu Sopandi (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
This study examines the effect of using mastery learning models on learning outcomes and collaboration skills of fifth-grade elementary school students. This quantitative study used the pre-experimental method with a one-group pretest-posttest design. This research involved 11 elementary school students from a school in Subang Regency. The research data were obtained using instruments in the form of multiple choice test sheets and descriptions given before and after treatment and collaboration skills observation sheets. Data analysis used descriptive statistics and inferential statistics, namely the normality test, homogeneity test and hypothesis testing paired sample t-test. From the research results, it is known that the t-test tcount is 21.133 > ttable 1.812. From these results, it can be seen that applying the mastery learning model has a significant influence on student learning outcomes. Acquisition of student collaboration skills obtained, starting from the criteria of being entirely collaborative to very collaborative. Then the use of mastery learning models affects student learning outcomes and student collaboration skills.